Sorbus megacarpa, a new combination in Chinese Rosaceae - Chen, Xin; Deng, Yunfei (Phytotaxa, 2012)
The genus Sorbus Linnaeus (1753: 477) in broad sense consists of about 250 species mainly distributed in the temperate regions of the Northern Hemisphere with 67 species in China (Phipps et al. 1990, Lu & Spongberg 2003, Kalkman 2004).